Molded adsorbent for canisters

KR103011749B1Active Publication Date: 2026-09-01NIPPON PAPER IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020237032739
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-24
Filing Date
2022-02-22
Publication Date
2026-09-01
Estimated Expiration
2042-02-22

Smart Images

  • Figure 112023105518470-PCT00008_ABST
    Figure 112023105518470-PCT00008_ABST
Patent Text Reader

Abstract

The objective is to provide an adsorbent using activated carbon fibers that is suitable for automotive canisters and has suppressed pressure loss. Furthermore, the objective is to provide a molded adsorbent that uses activated carbon fibers, has improved mechanical strength, and exhibits excellent effects as an adsorbent for canisters. The molded adsorbent for canisters satisfies the requirements of (1) to (3) below. (1) The molded adsorbent comprises an adsorbent containing activated carbon fibers and a binder. (2) The content ratio of the adsorbent containing activated carbon fibers and the binder is 0.3 to 20 parts by weight of the binder per 100 parts by weight of the adsorbent containing activated carbon fibers. (3) The fiber diameter of the activated carbon fibers is 13.0 μm or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a molded adsorbent suitable for canisters, and more specifically, to a molded adsorbent for canisters using activated carbon fibers. Background Technology

[0002] In gasoline vehicles, the pressure inside the fuel tank fluctuates due to changes in ambient temperature, and vaporized fuel gas filling the fuel tank is released from the fuel tank. The released vaporized fuel gas is considered to be one of the causative substances of PM2.5 or photochemical smog, and to prevent its release into the atmosphere, a canister equipped with an adsorbent such as activated carbon is provided (hereinafter, in this specification, a canister mounted in a vehicle may be abbreviated as "vehicle canister" or simply "canister").

[0003] With the recent rise in environmental conservation awareness, gas emission regulations tend to be tightened year by year, requiring higher adsorption performance for canisters. Furthermore, as the intake capacity of automobiles tends to be suppressed due to the widespread adoption of idling stop systems, gasoline adsorbed by the adsorbent in the canister tends to be difficult to desorb. Therefore, there is a need for additional high performance of the adsorbent used in canisters. Activated carbon is used as the adsorbent in canisters, and various forms such as granular, pellet, or honeycomb shapes have been proposed (e.g., Patent Document 1, etc.).

[0004] In contrast to the long-standing powdered and granular activated carbon, activated carbon fibers (or fibrous activated carbon) are sometimes referred to as third-generation activated carbon. Among activated carbons in a broad sense, activated carbon fibers are characterized by micropores directly opening on their outer surface and a tendency for rapid adsorption and desorption rates. However, activated carbon fibers have not yet been commercialized for use in canisters, and sufficient research and development have not yet been conducted to determine which characteristics make activated carbon fibers suitable for such applications.

[0005] As one of the adsorbents suitable for canisters, an activated carbon fiber sheet having specific characteristics has been proposed (Patent Document 2).

[0006] In addition, an activated carbon fiber molded adsorbent comprising activated carbon fibers and alkali-resistant fibrillated cellulose fibers has been proposed to improve the mechanical strength and packing density of a molded adsorbent using activated carbon fibers (e.g., Patent Document 3). Prior art literature

[0007] Japanese Patent Publication No. JP 2013-173137, Japanese Patent No. 6568328, Japanese Patent Publication No. JP 10-5580 The problem to be solved

[0008] As described above, attempts have been made to use activated carbon fibers as adsorbents for canisters, but activated carbon fibers are still under development as adsorbents for canisters. The inventors of the present invention conducted research with the goal of commercializing activated carbon fibers as adsorbents for automobile canisters and discovered that a sheet formed of activated carbon fibers is a practically suitable embodiment in terms of ease of handling and the need to secure the adsorbent so that it does not wear out due to vibrations during driving. However, they faced a problem in that if an activated carbon fiber sheet obtained by carbonization and reactivation as in the conventional method is filled into the interior of the adsorbent without providing a gap, the pressure loss of the canister increases.

[0009] Considering the above situation, one of the problems that the present invention aims to solve is to provide an adsorbent using activated carbon fibers that is suitable for canisters and has suppressed pressure loss.

[0010] In addition, another problem that the present invention aims to solve is to provide a molded adsorbent that uses activated carbon fibers, is resistant to shape collapse, and also exhibits excellent effects as an adsorbent for canisters. means of solving the problem

[0011] As a result of conducting thorough investigations, the inventors discovered that by manufacturing an activated carbon fiber material using fibers with a larger diameter than conventional fibers, air permeability is improved and pressure loss can be suppressed, thereby obtaining an adsorbent suitable for canisters. Furthermore, the inventors discovered that by mixing the activated carbon fiber material with a binder to form a molded body, pressure loss can be suppressed, and a molded adsorbent with improved mechanical strength and a shape that is resistant to collapse can be produced. Based on these findings, the present invention was completed. The present invention includes, for example, the following as means to solve problems that can be understood from various perspectives.

[0012] [1] As a molded adsorbent for canisters,

[0013] The above-mentioned molded adsorbent comprises an adsorbent containing activated carbon fibers and a binder, and

[0014] The content ratio of the adsorbent containing the activated carbon fiber and the binder is 0.3 to 20 parts by weight of binder per 100 parts by weight of the adsorbent containing the activated carbon fiber, and

[0015] A molded adsorbent having a fiber diameter of 13.0 μm or more of the activated carbon fiber.

[0016] [2] A molded adsorbent described in [1], wherein the fiber material serving as a precursor to the activated carbon fiber has a fineness of 4.0 to 60.0 dtex.

[0017] [3] A molded adsorbent described in [1] or [2], having a specific surface area of ​​1110 to 2300 m² / g of the activated carbon fiber.

[0018] [4] A molded adsorbent described in any one of [1] to [3], wherein the total pore volume of the activated carbon fiber is 0.50 to 1.20 cm³ / g.

[0019] [5] A molded adsorbent described in any one of [1] to [4], wherein the pore volume of the pores of the activated carbon fiber, having a pore diameter greater than 0.7 nm and less than or equal to 2.0 nm, is 0.20 to 1.20 cm³ / g.

[0020] [6] The ratio of the pore volume R of the activated carbon fiber above 0.7 / 2.0 This is 15% or more and less than 50%, and the above R 0.7 / 2.0 A molded adsorbent described in any one of [1] to [5], which is a ratio expressed as the pore volume of a pore with a diameter of 0.7 nm or less, which is occupied by the pore volume of a pore with a diameter of 2.0 nm or less.

[0021] [7] A canister having a molded adsorbent as described in any one of [1] to [6] above.

[0022] [8] The above canister is a canister for automobiles, as described in [7] above. Effects of the invention

[0023] According to one embodiment of the present invention, as an adsorbent using activated carbon fibers, an adsorbent suitable for canisters and having suppressed pressure loss can be provided.

[0024] In addition, according to one embodiment of the present invention, a molded adsorbent can be provided that uses activated carbon fibers, is a molded body that is resistant to collapse in shape, and also exhibits excellent effects as an adsorbent for canisters. Brief explanation of the drawing

[0025] [Fig. 1] Fig. 1 is a schematic diagram illustrating an example of a laminated adsorbent formed by stacking multiple sheet-like molded adsorbents, and an example of the direction of fluid flow passing through the laminated adsorbent. [Fig. 2] Fig. 2 is a drawing illustrating an example of an adsorbent formed into a disc shape. [Fig. 3] Fig. 3 is a drawing illustrating an example of an adsorbent formed into a cylindrical shape. Specific details for implementing the invention

[0026] The embodiments of the present invention will be described below. Also, unless specifically stated otherwise, the notation “AA~BB” regarding numerical ranges indicates “AA or greater and BB or less” (where “AA” and “BB” represent any numerical value). Also, unless specifically stated otherwise, the units of the lower and upper limits are the same as the unit immediately following the latter (i.e., “BB” here).

[0027] 1. Molded absorbent for canisters

[0028] The molded adsorbent of the present invention can be suitably used in a canister. A canister is a device equipped with an adsorbent that adsorbs vaporized fuel onto the adsorbent to prevent its release into the atmosphere, or, during engine operation, desorbs the vaporized fuel adsorbed onto the adsorbent and supplies it to the engine. Canisters are generally used in machinery or devices equipped with internal combustion engines that use fuel containing highly volatile hydrocarbons, such as vehicles and ships equipped with internal combustion engines. Examples of vehicles include automobiles that use gasoline as fuel. Examples of ships include boats that use gasoline as fuel.

[0029] A molded adsorbent, which is one embodiment of the present invention, may be a molded body comprising an adsorbent containing activated carbon fibers and a binder. The "adsorbent containing activated carbon fibers" may be an activated carbon fiber alone. Being composed of an activated carbon fiber alone corresponds to the case where the entire "adsorbent containing activated carbon fibers" is composed entirely of activated carbon fibers. Furthermore, the "adsorbent containing activated carbon fibers" may include other adsorbents, and other adsorbents may include porous materials such as zeolites, silica gel, activated alumina, and metal organic frameworks (MOFs), preferably types of activated carbon other than activated carbon fibers, such as granular activated carbon. That is, as another embodiment, the material constituting the "adsorbent containing activated carbon fibers" may be a mixture containing an adsorbent such as a material belonging to the broad category of activated carbons.

[0030] A molded adsorbent, which is one embodiment of the present invention, includes activated carbon fibers as an adsorbent and can therefore be described as a molded body comprising activated carbon fibers and a binder. In other words, it can be described as an adsorbent obtained by molding activated carbon fibers using a binder. By incorporating a binder in addition to activated carbon fibers and molding, a molded body can be obtained in which mechanical strength is improved and the shape is resistant to collapse.

[0031] In one embodiment of the present invention, a binder is used as one component constituting a molded adsorbent. The binder that can be used is preferably a binder that does not clog the pores of the activated carbon fiber and the activated carbon. Examples of materials include polyvinyl alcohol-based aqueous solutions. Additionally, fibrous binders may be used as preferred examples of binders. Polyvinyl alcohol-based fibrous binders may be used as moist heat bonding types. Furthermore, composite fibers such as core fibers, parallel fibers, and radially split fibers may also be used. Specifically, combinations such as polypropylene (core) and polyethylene (sheath), polypropylene (core) and ethylene vinyl alcohol (sheath), high melting point polyester (core) and low melting point polyester (sheath), and high melting point polyester (core) and polyethylene (sheath) may be used.

[0032] In addition, fibers composed solely of polyethylene or polypropylene can be used as a fully fused type. Furthermore, fibrillated fibrous binders can also be used. As long as the activated carbon fibers and granular activated carbon can be bound and formed by fibrillation, there are no particular limitations. They can be widely used regardless of whether they are synthetic or natural products. Examples of such fibrillated fibrous binders include acrylic fibers, polyethylene fibers, polypropylene fibers, polyacrylonitrile fibers, cellulose fibers, nylon fibers, aramid fibers, etc.

[0033] In a molded adsorbent, the content ratio of the binder to the adsorbent containing activated carbon fibers may be, for example, 0.3 to 20 parts by weight of binder per 100 parts by weight of the adsorbent containing activated carbon fibers. The lower limit of the binder may preferably be 0.5 parts by weight, 0.8 parts by weight, 1.0 parts by weight, 2.0 parts by weight, or 3.0 parts by weight. Additionally, the upper limit of the binder may preferably be 18 parts by weight, 15 parts by weight, or 10 parts by weight. As described above, by using these content ratios, the molded adsorbent can be formulated to achieve both mechanical strength and adsorption / desorption performance. If mechanical strength is to be increased, the amount of binder may be increased, and if adsorption / desorption performance is to be prioritized, the amount of binder may be set lower.

[0034] In addition, as another embodiment, the above content ratio may also be applied when the adsorbent containing activated carbon fibers is a mixture of activated carbon fibers and granular activated carbon. That is, in the molded adsorbent, the content ratio of the mixture of activated carbon fibers and granular activated carbon to the binder may be, for example, 0.3 to 20 parts by weight of binder per 100 parts by weight of the mixture of activated carbon fibers and granular activated carbon. The lower limit of the binder may preferably be 0.5 parts by weight, 0.8 parts by weight, 1.0 parts by weight, 2.0 parts by weight, or 3.0 parts by weight. In addition, the upper limit of the binder may preferably be 18 parts by weight, 15 parts by weight, or 10 parts by weight. As described above, by using these content ratios, the molded adsorbent can be formulated to achieve both mechanical strength and adsorption / desorption performance. If mechanical strength is to be increased, the amount of binder may be increased, and if adsorption / desorption performance is to be prioritized, the amount of binder may be set lower.

[0035] By using a binder in the above-mentioned ratio, it is possible to avoid the clogging of the pores of the activated carbon fibers, which would lead to a decrease in properties such as adsorption-desorption performance or pressure loss, and to maintain the excellent properties of the activated carbon fibers, thereby obtaining a molded adsorbent with excellent properties.

[0036] The molded adsorbent of one embodiment of the present invention does not exclude the inclusion of components other than activated carbon fibers and a binder, but the addition of other components should be permitted within a range that does not impede the suppression of pressure loss. For example, particulate activated carbon, etc., may be added.

[0037] <Fiber diameter of activated carbon fiber>

[0038] The lower limit of the fiber diameter of the activated carbon fiber that can be used in the molded adsorbent of the present invention may preferably be 13.0 μm or more, more preferably 14.0 μm or more, and even more preferably 15.0, 16.0, 17.0, 18.0, 19.0, or 20.0 μm or more.

[0039] The upper limit of the fiber diameter constituting the activated carbon fiber sheet of the present invention may be arbitrary from the perspective of suppressing pressure loss, but considering the balance with adsorption and desorption performance, it may be, for example, 60.0 μm or less, preferably 55.0 μm or less, more preferably 50.0, 45.0, 40.0, or 35.0 μm.

[0040] If the fiber diameter of the fiber constituting the activated carbon fiber is within the above range, it can be made into an activated carbon fiber capable of further suppressing pressure loss.

[0041] <Fiber Length and Average Value of Activated Carbon Fibers>

[0042] The lower limit of the fiber length of the activated carbon fiber that can be used in the molded adsorbent of the present invention may preferably be 300 or more, more preferably 500, 600, 700, 800, 850, 900 or more, and even more preferably 950 or more.

[0043] The upper limit of the fiber length constituting the activated carbon fiber sheet of the present invention may preferably be 5000 or less, more preferably 4000, 3000, 2500, 2000, 1500 or less, and even more preferably 1200 or less.

[0044] If the fiber length of the fiber constituting the activated carbon fiber is within the above range, it can be made into an activated carbon fiber capable of further suppressing pressure loss.

[0045] <Fiber Length and Coefficient of Variation of Activated Carbon Fibers>

[0046] The lower limit of the coefficient of variation of fiber length of the activated carbon fiber that can be used in the molded adsorbent of the present invention may preferably be 0.1 or higher, more preferably 0.2, 0.3, 0.4, 0.5 or higher, and even more preferably 0.6 or higher.

[0047] The upper limit of the coefficient of variation of fiber length constituting the activated carbon fiber sheet of the present invention may preferably be 2.5 or less, more preferably 2.0, 1.5, 1.0, 0.9, 0.8 or less, and even more preferably 0.7 or less.

[0048] If the fiber length of the fiber constituting the activated carbon fiber is within the above range, it can be made into an activated carbon fiber capable of further suppressing pressure loss.

[0049] Fineness of activated carbon fiber precursors

[0050] To obtain activated carbon fibers with the fiber diameter described above, it is suitable for the fiber diameter (as fineness) of the fiber serving as a precursor to the activated carbon fiber to be within the following range. That is, using a fiber as a precursor as described below is suitable for obtaining activated carbon fibers capable of suppressing pressure loss.

[0051] The lower limit of the fiber diameter (as fineness) of the fiber serving as a precursor may preferably be 4.0 dtex or more, more preferably 5.0 dtex or more, and even more preferably 8.0, 10.0, 12.0, or 15.0 dtex or more.

[0052] The upper limit of the fiber diameter (as fineness) of the fiber serving as a precursor may preferably be 60.0 dtex or less, more preferably 50.0 dtex or less, even more preferably 40.0, or 30.0 dtex or less.

[0053] The activated carbon fibers that can be used in the molded adsorbent of the present invention may also be made into more preferred embodiments by satisfying at least one or any two or more of the following specified items.

[0054] Specific surface area

[0055] The lower limit of the specific surface area of ​​the activated carbon fiber that can be used in the molded adsorbent of the present invention may preferably be 1100 m² / g or more, more preferably 1200 m² / g or more, and even more preferably 1300, 1400, 1500, 1600, 1700, or 1800 m² / g or more.

[0056] The specific surface area of ​​the activated carbon fiber that can be used in the molded adsorbent of the present invention is generally preferred to be larger in terms of adsorption and desorption performance, but in the case of an adsorbent for a canister, the upper limit of the specific surface area may generally be 2400, 2300, 2200, or 2100 m² / g or less.

[0057] By making the specific surface area within the range described above, a molded adsorbent with superior adsorption and desorption performance for vaporized fuel gas can be produced. In addition, in one embodiment of the present invention, as an adsorbent material used in such a canister, it is possible to achieve a reduction in pressure loss in the canister while maintaining a large specific surface area.

[0058] <Total Crafting Volume>

[0059] The lower limit of the total pore volume of the activated carbon fiber that can be used in the molded adsorbent of the present invention may preferably be 0.50 cm³ / g or more, more preferably 0.60 cm³ / g or more, and even more preferably 0.70, 0.80, or 0.90 cm³ / g or more.

[0060] The upper limit of the total pore volume of the activated carbon fiber that can be used in the molded adsorbent of the present invention may preferably be 1.20 cm³ / g or less, more preferably 1.10 cm³ / g or less, and even more preferably 1.00 cm³ / g or less.

[0061] By making the total pore volume within the range described above, it is possible to make a molded adsorbent with superior adsorption and desorption performance for vaporized fuel gas.

[0062] <Average pore diameter (Average pore diameter)>

[0063] With respect to the present invention, the term “hole diameter” means the diameter or width of a hole, not the radius of the hole, unless specifically stated otherwise.

[0064] The lower limit of the average pore diameter of the activated carbon fiber that can be used in the molded adsorbent of the present invention may preferably be 1.69 nm or more, more preferably 1.70 nm or more, and even more preferably 1.72, 1.75, 1.78, or 1.80 nm or more.

[0065] The upper limit of the average pore diameter of the activated carbon fiber that can be used in the molded adsorbent of the present invention may be arbitrary, but preferably 4.00 nm or less, more preferably 3.50 nm or less, and even more preferably 3.00 nm or less.

[0066] By setting the average pore diameter to the range described above, it is possible to make a molded adsorbent with superior adsorption and desorption performance for transpiration fuel gas.

[0067] Ultramicroscopic volume: V 0.7 >

[0068] In the present invention, the term "ultramicropore" refers to a pore with a pore diameter of 0.7 nm or less.

[0069] The lower limit of the volume of the ultramicrospheres of the activated carbon fibers that can be used in the molded adsorbent of the present invention may preferably be 0.05 cm³ / g or more, more preferably 0.10 cm³ / g or more, even more preferably 0.12, or 0.14 cm³ / g or more.

[0070] The upper limit of the volume of the ultramicropores of the activated carbon fibers that can be used in the molded adsorbent of the present invention may preferably be 0.30 cm³ / g or less, more preferably 0.29 cm³ / g or less, and even more preferably 0.26, 0.24, 0.22, or 0.20 cm³ / g or less.

[0071] By setting the volume of the ultramicro pores to the range described above, it is possible to make a molded adsorbent with superior adsorption and desorption performance for vaporized fuel gas.

[0072] Microsphere volume: V 2.0 >

[0073] In the present invention, the term "micropore" refers to a pore with a pore diameter of 2.0 nm or less.

[0074] The lower limit of the micropore volume of the activated carbon fiber that can be used in the molded adsorbent of the present invention may preferably be 0.50 cm³ / g or more, more preferably 0.60 cm³ / g or more, even more preferably 0.65, or 0.70 cm³ / g or more.

[0075] The upper limit of the micropore volume of the activated carbon fiber that can be used in the molded adsorbent of the present invention may preferably be 1.00 cm³ / g or less, more preferably 0.90 cm³ / g or less, and even more preferably 0.80 cm³ / g or less.

[0076] By setting the micropore volume to the range described above, it is possible to make a molded adsorbent with superior adsorption and desorption performance for fuel gas.

[0077] Pore ​​volume of pores with a diameter greater than 0.7 nm and less than or equal to 2.0 nm: V 0.7-2.0 >

[0078] Pore ​​volume V of pores with a diameter greater than 0.7 nm and less than or equal to 2.0 nm 0.7-2.0 It can be obtained by the following Equation 1 using the value of the ultramicropore volume a and the value of the micropore volume b.

[0079] V 0.7-2.0 = b - a … Equation 1

[0080] In an activated carbon fiber usable in the molded adsorbent of the present invention, the pore volume V of pores having a pore diameter greater than 0.7 nm and less than or equal to 2.0 nm 0.7-2.0 The lower limit of may preferably be 0.20 cm³ / g or more, more preferably 0.30 cm³ / g or more, and even more preferably 0.36, 0.40, 0.45, or 0.50 cm³ / g or more.

[0081] In an activated carbon fiber usable in the molded adsorbent of the present invention, the pore volume V of pores having a pore diameter greater than 0.7 nm and less than or equal to 2.0 nm 0.7-2.0The upper limit of may preferably be 1.20 cm³ / g or less, more preferably 1.00 cm³ / g or less, and even more preferably 0.90, 0.80, 0.75, 0.70, 0.65, or 0.60 cm³ / g or less.

[0082] Current crafting volume V 0.7-2.0 By making the range as described above, it is possible to make a molded adsorbent with superior adsorption and desorption performance for fuel gas.

[0083] Proportion of the volume of ultramicrospheres in the volume of microspheres: R 0.7 / 2.0 >

[0084] R, the proportion of the pore volume of ultramicropores with a pore diameter of 0.7 nm or less occupied by the pore volume of micropores with a pore diameter of 2.0 nm or less 0.7 / 2.0 It can be obtained by the following Equation 2 using the value of the ultramicropore volume a and the value of the micropore volume b.

[0085] R 0.7 / 2.0 = a / b × 100(%) … Equation 2

[0086] In the activated carbon fibers usable in the molded adsorbent of the present invention, the ratio of the ultramicropore volume to the micropore volume R 0.7 / 2.0 The lower limit of may preferably be 15.0% or more, more preferably 18% or more, and even more preferably 19% or more.

[0087] In the activated carbon fibers usable in the molded adsorbent of the present invention, the ratio of the ultramicropore volume to the micropore volume R 0.7 / 2.0 The upper limit of may preferably be 60% or less, more preferably 50% or less, and even more preferably 40, 30, or 25% or less.

[0088] R of the existence ratio of the corresponding ultramicropore volume 0.7 / 2.0By making the range as described above, it is possible to make a molded adsorbent with superior adsorption and desorption performance for fuel gas.

[0089] <Dry Density>

[0090] The lower limit of the dry density of the molded adsorbent of the present invention may preferably be 0.010 g / cm³ or higher, more preferably 0.015 g / cm³ or higher, and even more preferably 0.020, 0.030, 0.040, 0.050, or 0.060 g / cm³ or higher.

[0091] The upper limit of the dry density of the molded adsorbent of the present invention may preferably be 0.400 g / cm³ or less, more preferably 0.300 g / cm³ or less, and even more preferably 0.200, 0.150, 0.140, 0.130, 0.120, 0.110, or 0.100 g / cm³ or less.

[0092] By setting the dry density to the range described above, it is possible to produce a molded adsorbent with superior adsorption-desorption performance per volume required for canisters within the capacity range of the adsorbent that can be accommodated in the canister. Furthermore, by setting it above the lower limit, it is possible to avoid a decrease in mechanical properties (e.g., strength, etc.). Additionally, the dry density of the molded adsorbent can be adjusted by the fiber diameter of the carbon fiber, the fiber length by adjusting the stirring force during carbon fiber disintegration, and the increase or decrease of the suction force when suction molding the mixed slurry with the binder, thereby suppressing pressure loss of the molded adsorbent.

[0093] Moisture content

[0094] The molded adsorbent of the present invention is suitable for having a predetermined moisture content. For example, the lower limit of the moisture content under conditions of 23°C and 50% relative humidity may preferably be 1.0% or more, more preferably 2.0% or more, and even more preferably 3.0% or more.

[0095] In addition, the upper limit of the moisture content under conditions of 23°C and 50% relative humidity may preferably be 30.0% or 25.0% or less, more preferably 20.0% or less or 15.0% or less, and even more preferably 10.0% or 8.0% or less.

[0096] By making the moisture content under the above conditions within the above range, it is possible to produce a molded adsorbent that is superior as an adsorbent for automobile canisters.

[0097] <n-부탄 흡탈착 성능>

[0098] The molded adsorbent of the present invention preferably has a predetermined n-butane adsorption and desorption performance as an adsorbent. Since the n-butane adsorption and desorption performance serves as an indicator of the adsorption and desorption performance of vaporized gas, excellent n-butane adsorption and desorption performance is suitable for use in automobile canisters. The n-butane adsorption and desorption performance can be expressed as the effective adsorption rate of n-butane per molded adsorbent, which is the amount of adsorption when adsorption is repeated after the n-butane is sufficiently absorbed and broken down, then detached from the adsorbent under predetermined desorption conditions.

[0099] As a preferred form of the molded adsorbent of the present invention, the effective adsorption / desorption rate of n-butane obtained according to the measurement method shown in the following examples may preferably be 6.00 wt% or more, more preferably 6.25 wt% or more, and even more preferably 6.50, 6.75, or 7.00 wt% or more.

[0100] In addition, as a preferred embodiment of the adsorption molded body of the present invention, the effective adsorption-desorption rate of n-butane obtained according to the measurement method shown in the following examples may preferably be 25.0% or more, more preferably 30.0% or more, and even more preferably 40.0, 50.0, 60.0, 70.0, or 75.0% or more. An adsorbent having such an adsorption-desorption rate is suitable for canisters, particularly for automobile canisters.

[0101] <0ppm retention time>

[0102] In addition, as a preferred embodiment of the adsorption molded body of the present invention, the 0 ppm retention time obtained according to the measurement method shown in the following examples may preferably be 15 minutes or 30 minutes or more, more preferably 40 minutes or more, and even more preferably 50 minutes, 55 minutes, 60 minutes, 65 minutes, 68 minutes, 69 minutes, or 70 minutes or more.

[0103] The longer the 0 ppm maintenance time, the longer the time until the adsorbent begins to release the adsorbed substance. Therefore, the 0 ppm maintenance time serves as an indicator of the strength of the adsorption capacity.

[0104] The molded adsorbent for a canister according to the present invention is suitable for use in a canister mounted in an automobile. For such a molded adsorbent, it is desirable that pressure loss is suppressed. The upper limit of pressure loss may preferably be 1.50 kPa or less, more preferably 1.20 kPa or less, and even more preferably 1.10, 1.00, 0.90, 0.80, or 0.70 kPa or less. It is not desirable for pressure loss to be lower, but from the perspective of the original purpose, such as adsorption performance, the lower limit of pressure loss may preferably be 0.05 kPa or more, more preferably 0.10 kPa or more, and even more preferably 0.15 kPa or more.

[0105] 2. Shape of the molded adsorbent

[0106] In one embodiment of the present invention, the shape of the molded adsorbent is not particularly limited, and, for example, a shape that can be molded and allows gas to flow is suitable. Specific shapes include, for example, a columnar shape having a cross-sectional shape such as a circle or a polygon, a truncated shape such as a truncated cone or a polygonal truncated cone, and a pellet shape and a honeycomb shape, and preferably, a cylindrical shape and a rectangular parallelepiped shape. In addition, a disc-shaped, sheet-shaped, or plate-shaped molded adsorbent may be formed into a laminate by stacking multiple such adsorbents. Various embodiments are shown in FIGS. 1 to 3. Furthermore, dimensions such as length and thickness in the drawings are schematically represented to facilitate understanding of the invention and are not limited thereto.

[0107] The laminated adsorbent (1) shown in FIG. 1 is a laminate formed by stacking four sheet-shaped molded adsorbents (10). The sheet-shaped molded adsorbents (10) are formed by stacking the main surfaces (10a) of the sheets together.

[0108] The method of housing the laminated adsorbent (1) within the canister is optional. As a preferred embodiment, the direction in which the tensile strength of the sheet is strong may be arranged to follow the flow of the gas. Furthermore, more specifically, to exemplify a preferred embodiment, it is preferable that the main surface (10a) of the sheet-shaped molded adsorbent is not oriented in a direction orthogonal to the flow direction of the fluid (F), such as vaporized gas, and more preferably, as shown in FIG. 1, the main surface (a) may be arranged to be approximately parallel to the flow direction of the fluid (F), such as vaporized gas. By arranging the main surface (a) to be approximately parallel to the flow direction of the fluid (F), such as vaporized gas, the side cross-sections (10b) of the plurality of sheet-shaped molded adsorbents are arranged to face the flow direction of the fluid (F). By arranging them in this way, pressure loss can be reduced. In FIG. 1, the shorter side section (10b) faces the direction of flow of the fluid (F), but is not limited thereto, and the longer side section (10c) may also face the direction of flow of the fluid (F).

[0109] In addition, the adsorption laminate may be in the shape of a rectangular prism or a cube overall. Furthermore, it may be shaped to fit the shape of the adsorption chamber housing the adsorption laminate.

[0110] FIG. 2 illustrates another embodiment of the present invention. In the embodiment illustrated in FIG. 2, the molded adsorbent is molded into a disc shape. The disc-shaped molded adsorbent may be overlapped to form a cylindrical shape.

[0111] FIG. 3 illustrates another embodiment of the present invention. In the embodiment illustrated in FIG. 3, the molded adsorbent is integrally molded as a cylindrical molded body.

[0112] As such, the molded adsorbent of the present invention is a material that can be easily processed or molded into various shapes and has excellent handling properties.

[0113] 3. Canister

[0114] The molded adsorbent of the present invention is suitable as an adsorbent housed in an automobile canister. That is, as another embodiment, the present invention may also provide an automobile canister.

[0115] The automobile canister of the present invention is equipped with a molded adsorbent as an adsorbent. There are no particular restrictions on the structure of the automobile canister, and a general structure may be adopted. For example, the automobile canister may have a structure as described below.

[0116] Housing and,

[0117] An adsorbent chamber for storing adsorbents within the housing, and

[0118] A first opening for communicating gas so as to move between the adsorbent chamber and the engine, and

[0119] A second opening for communicating gas so as to move between the adsorbent chamber and the fuel tank, and

[0120] A third opening that opens when a predetermined pressure is applied from the adsorption chamber or the outside air, and is configured to communicate between the adsorption chamber and the outside air in a way that allows gas to move.

[0121] A canister equipped with

[0122] In the canister of the present invention, the molded adsorbent of the present invention may be used as an adsorbent. As described above, since the molded adsorbent of the present invention can reduce pressure loss, pressure loss can be suppressed even when filled without gaps, compared to cases where conventional activated carbon fiber sheets are filled.

[0123] The first, second, and third openings are each gas outlets for gas entry and exit. The arrangement of each opening serving as a gas outlet is not particularly limited, but the third opening serving as an outside air outlet is preferably positioned so that the gas can sufficiently pass through the adsorbent when the gas moves between the first and / or second openings. For example, embodiments may be adopted such as providing the first and second openings on the first side portion of the housing and providing the third opening on the second side portion located opposite the first side portion.

[0124] The adsorbent chamber may be provided by dividing it into multiple chambers. For example, the adsorbent chamber may be divided into two or more sections by partitions. As partitions, a perforated plate with airtightness may be used. Additionally, a second external housing may be provided separately from the first housing, and the first housing and the second housing may be connected through a gas passage to provide additional adsorbent chambers. When multiple sections or housings are provided in this manner, as a preferred embodiment, adsorbents or adsorbent chambers may be arranged such that the adsorption capacity decreases sequentially from a first or second opening through which gas is introduced from the engine or fuel tank toward a third opening, in each section or housing unit.

[0125] As a specific example, a composite canister may be exemplified having a main body canister (first housing) and a second canister (second housing) attached to the outside air inlet side thereof. When providing multiple compartments or housings in this manner, the compartment or housing into which vaporized gas from the engine or fuel tank first enters is designated as the main body (first compartment or first housing) having the largest storage volume, and conventional low-cost activated carbon is stored in said main body, while the molded adsorbent of the present invention, which has excellent low-concentration adsorption and desorption performance, is stored in the second compartment or second housing having a relatively smaller storage volume thereafter, thereby making it possible to produce a high-performance canister while suppressing costs.

[0126] In the case where there are multiple adsorbent chambers, the concentration of vaporized fuel gas flowing in from the front layer becomes lower in the adsorbent chamber located further downstream from the engine or fuel tank (i.e., the adsorbent chamber positioned closer to the external air inlet / outlet). Therefore, the molded adsorbent of the present invention, which has a high n-butane adsorption capacity at a low concentration of about 0.2%, is suitable as an adsorbent to be housed in a second compartment or second housing located further downstream from the engine or fuel tank, or in an adsorbent chamber located further downstream therefrom. Furthermore, when the molded adsorbent of the present invention is used in an adsorbent chamber closer to the external air inlet, the activated carbon fiber sheet of the present invention is suitable as an adsorbent for use in an automobile canister in that it can reduce the amount of leakage of vaporized fuel gas when the vehicle is stopped for a long time, as the effective adsorption / desorption amount by purging is high.

[0127] Accordingly, as one embodiment of a preferred canister, for example, the following form may be cited.

[0128] As an automotive canister having two or more adsorbent chambers,

[0129] A canister for an automobile in which a molded adsorbent of the present invention is housed in a second or subsequent adsorbent chamber positioned further downstream than a first adsorbent chamber into which gas is first introduced from an engine or fuel tank.

[0130] In the above form, there may be two adsorbent chambers or more. In addition, if there are three or more adsorbent chambers, the molded adsorbent of the present invention may be housed in at least one adsorbent chamber after the second adsorbent chamber.

[0131] 4. Method for manufacturing a molded adsorbent

[0132] The activated carbon fibers used in the present invention can be manufactured by carbonizing and reactivating fibers having a predetermined fiber diameter. Additionally, fibers prior to carbonization and reactivation are referred to as precursor fibers, and a sheet formed from precursor fibers is referred to as a precursor fiber sheet. In relation to the present invention, the term "fiber diameter" refers to the diameter or width of the fiber, rather than the radius of the fiber, unless specifically stated otherwise. Furthermore, the term "fiber diameter" is primarily used for fibers of the activated carbon fiber after carbonization and reactivation.

[0133] Hereinafter, an embodiment for manufacturing an activated carbon fiber sheet is exemplified as a method for manufacturing activated carbon fibers. As a preferred embodiment of the method for manufacturing an activated carbon fiber sheet, the following method may be cited as an example.

[0134] The method includes carbonizing and reactivating a precursor fiber sheet that retains either or both of a phosphoric acid-based catalyst or an organic sulfonic acid-based catalyst, and

[0135] A method in which the precursor fiber sheet comprises cellulose-based fibers, and the fiber diameter of the fibers is 4.0 to 60.0 dtex.

[0136] The lower limit of the fiber diameter (as fineness) of the fiber serving as a precursor may preferably be 4.0 dtex or more, more preferably 5.0 dtex or more, and even more preferably 8.0, 10.0, 12.0, or 15.0 dtex or more.

[0137] The upper limit of the fiber diameter (as fineness) of the fiber serving as a precursor may preferably be 60.0 dtex or less, more preferably 50.0 dtex or less, even more preferably 40.0, or 30.0 dtex or less.

[0138] If the fiber diameter of the fiber serving as the precursor is within the above range, it can be made into an activated carbon fiber sheet capable of further suppressing pressure loss.

[0139] A method for manufacturing a sheet-like activated carbon fiber that can be used in the present invention can be carried out, for example, by referring to the information below.

[0140] 4-1. Preparation of Raw Material Sheets (Precursor Fiber Sheets)

[0141] Types of Fibers

[0142] Examples of fibers constituting the raw material sheet include cellulose-based fibers, pitch-based fibers, PAN-based fibers, phenolic resin-based fibers, etc., and preferably, cellulose-based fibers.

[0143] Cellulose fibers

[0144] Cellulose-based fibers are fibers composed primarily of cellulose and / or its derivatives. Cellulose and cellulose derivatives may be of any origin, such as chemically synthesized products, plant-derived products, regenerated cellulose, or cellulose produced by bacteria. Preferably, as cellulose-based fibers, fibers formed from plant-based cellulose materials obtained from trees, etc., and fibers composed of long fibrous regenerated cellulose materials obtained by chemically treating and dissolving plant-based cellulose materials (cotton, pulp, etc.) may be used. Furthermore, it is acceptable for these fibers to contain components such as lignin or hemicellulose.

[0145] As raw materials for cellulose-based fibers (plant-based cellulose materials, regenerated cellulose materials), examples include plant-based cellulose fibers such as cotton (short fiber cotton, medium fiber cotton, long fiber cotton, super-long cotton, super-super-long cotton, etc.), hemp, bamboo, paper mulberry, three-branched paper mulberry, banana, and fibrous plants; regenerated cellulose fibers such as copper-ammonium rayon, viscose rayon, polynosic rayon, and cellulose made from bamboo; purified cellulose fibers spun with an organic solvent (N-methylmorpholine N-oxide); and acetate fibers such as diacetate or triacetate. Among these, it is preferable to select at least one type from copper-ammonium rayon, viscose rayon, and purified cellulose fibers for ease of availability.

[0146] The form of the cellulose-based fiber is not particularly limited, and depending on the purpose, it may be used in the form of raw yarn (unprocessed yarn), twisted yarn, dyed yarn, single yarn, plied yarn, covering yarn, etc. In addition, if the cellulose-based fiber contains two or more types of raw materials, it may be used as a blended yarn or a mixed yarn. Furthermore, as a cellulose-based fiber, the various forms of raw materials mentioned above may be used individually or in combination of two or more types. Among these, untwisted yarn is preferred to ensure compatibility between the moldability and mechanical strength of the composite material.

[0147] Fiber Sheet

[0148] Fiber sheets refer to materials processed from a number of fibers into a thin, wide sheet, and include woven fabrics, knitted fabrics, nonwoven fabrics, etc.

[0149] There are no specific restrictions on the method of weaving cellulose-based fibers, and general methods can be used. Additionally, there are no specific restrictions on the weave structure of the fabric, and plain weave, twill weave, and satin weave can be used.

[0150] In a fabric formed from cellulose fibers, the gap between the warp and weft threads of the cellulose fibers may preferably be 0.1 to 0.8 mm, more preferably 0.2 to 0.6 mm, and even more preferably 0.25 to 0.5 mm. In addition, the weight per unit area of ​​the fabric made from cellulose fibers may preferably be 50 to 500 g / m², and more preferably 100 to 400 g / m².

[0151] By making the cellulose-based fibers and the fabric composed of cellulose-based fibers within the above range, the carbon fiber fabric obtained by heat-treating this fabric can be made to have excellent strength.

[0152] The method of manufacturing the nonwoven fabric is not particularly limited, but examples include a method of obtaining a fiber sheet using a dry method or a wet method with the aforementioned fibers cut to a suitable length as raw materials, or a method of obtaining a fiber sheet directly from a solution using an electrospinning method. In addition, after obtaining the nonwoven fabric, treatment by resin bonding, thermal bonding, spunlace, needle punching, etc. may be applied for the purpose of bonding the fibers together.

[0153] 4-2. Catalyst

[0154] In Example 1 of the manufacturing method, a catalyst is retained in a raw material sheet prepared as described above. A carbonization treatment is performed by retaining the catalyst in the raw material sheet, and further reactivation is carried out using steam, carbon dioxide, air gas, etc., to obtain a porous activated carbon fiber sheet. As a catalyst, for example, a phosphate-based catalyst, an organic sulfonic acid-based catalyst, etc. can be used.

[0155] Phosphate-based catalysts

[0156] Examples of phosphoric acid-based catalysts include phosphoric oxy acids such as phosphoric acid, metaphosphoric acid, pyrophosphoric acid, phosphonic acid, aphosphonic acid, and phosphinic acid; diammonium hydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate; dimethylphosphonopropanamide, ammonium polyphosphate, polyphosphonitrile chloride; and condensates of phosphoric acid, tetrakis(hydroxymethyl)phosphonium salt or tris(1-aziridinyl)phosphine oxide with urea, thiourea, melamine, guanine, cyanamide, hydrazine, dicyandiamide or methylol derivatives thereof, and preferably diammonium hydrogen phosphate. One type of phosphoric acid-based catalyst may be used alone or two or more types may be used in combination. When a phosphate-based catalyst is used as an aqueous solution, the concentration may preferably be 0.05 to 2.0 mol / L, and more preferably 0.1 to 1.0 mol / L.

[0157] Organic sulfonic acid catalysts

[0158] As an organic sulfonic acid, an organic compound having one or more sulfo groups can be used, and, for example, compounds in which sulfo groups are bonded to various carbon skeletons such as aliphatic or aromatic types can be used. As for the organic sulfonic acid catalyst, a low molecular weight one is preferred from the perspective of handling.

[0159] Examples of organic sulfonic acid catalysts include compounds represented by R-SO3H (wherein R represents a straight-chain / branched alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and the alkyl group, cycloalkyl group, and aryl group may each be substituted with an alkyl group, a hydroxyl group, or a halogen group). Examples of organic sulfonic acid catalysts include methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, 1-hexanesulfonic acid, vinylsulfonic acid, cyclohexanesulfonic acid, p-toluenesulfonic acid, p-phenolsulfonic acid, naphthalenesulfonic acid, benzenesulfonic acid, camphorsulfonic acid, etc. Among these, methanesulfonic acid may preferably be used. In addition, one type of organic sulfonic acid catalyst may be used alone, or two or more types may be used in combination.

[0160] When using an organic sulfonic acid as an aqueous solution, its concentration may preferably be 0.05 to 2.0 mol / L, and more preferably 0.1 to 1.0 mol / L.

[0161] Mixed Catalyst

[0162] The above phosphate-based catalyst and organic sulfonic acid-based catalyst may be mixed and used as a mixed catalyst. The mixing ratio may be adjusted appropriately.

[0163] Catalyst's pussy

[0164] The catalyst is retained on the raw material sheet. Here, "retention" means maintaining the state in which the catalyst is in contact with the raw material sheet, and this can take various forms such as attachment, adsorption, or impregnation. The method of retaining the catalyst is not particularly limited, but examples include immersion in an aqueous solution containing the catalyst, spraying an aqueous solution containing the catalyst onto the raw material sheet, contacting it with vaporized catalyst vapor, or mixing the fibers of the raw material sheet with an aqueous solution containing the catalyst to form a paper.

[0165] In terms of sufficient carbonization, a method may preferably be used in which the raw material sheet is immersed in an aqueous solution containing a catalyst to impregnate the catalyst into the fibers. The temperature at which the sheet is immersed in the aqueous solution containing the catalyst is not particularly limited, but room temperature is preferred. The immersion time is preferably 10 seconds to 120 minutes, more preferably 20 seconds to 30 minutes. By immersion, for example, 1 to 150 mass%, preferably 5 to 60 mass% of the catalyst is adsorbed onto the fibers constituting the raw material sheet. After immersion, it is preferable to remove the raw material sheet and dry it. Any drying method is acceptable, such as leaving it at room temperature or introducing it into a dryer. Drying should be performed after removing the sheet from the aqueous solution containing the catalyst until the excess moisture evaporates and there is no change in the weight of the sample. For example, in room temperature drying, the drying time should be left for at least 0.5 days. After the mass change is almost eliminated by drying, the process proceeds to carbonizing the raw material sheet containing the catalyst.

[0166] 4-3. Carbonization Treatment

[0167] After preparing a raw material sheet containing a catalyst, the sheet is subjected to carbonization treatment. The carbonization treatment to obtain an activated carbon fiber sheet can be performed according to a general method for carbonizing activated carbon, but as a preferred embodiment, it can be performed as follows.

[0168] Carbonization treatment is typically performed in an inert gas atmosphere. In the present invention, an inert gas atmosphere refers to an oxygen-free or low-oxygen atmosphere in which carbon is difficult to combust and thus carbonizes, and preferably, it may be a gas atmosphere such as, for example, argon or nitrogen.

[0169] The raw material sheet containing the catalyst is heated and carbonized in the aforementioned predetermined gas atmosphere.

[0170] The lower limit of the heating temperature may preferably be 300°C or higher, more preferably 350°C or higher, even more preferably 400°C or higher, or 750°C or higher.

[0171] The upper limit of the heating temperature may preferably be 1400°C or lower, more preferably 1300°C or lower, even more preferably 1200°C or lower, or 1000°C or lower.

[0172] By setting the heating temperature in this way, a carbon fiber sheet with the fiber shape maintained can be obtained. If the heating temperature is below the above lower limit, the carbonization is likely to be insufficient, with the carbon content of the carbon fiber being 80% or less.

[0173] The lower limit of the heat treatment time includes the time for heating, and may be preferably 10 minutes or more, more preferably 11 minutes or more, even more preferably 12 minutes, 15 minutes, 20 minutes, 25 minutes or more, and more preferably 30 minutes or more.

[0174] The upper limit of the heat treatment time may be arbitrary, but preferably 180 minutes or less, more preferably 160 minutes, and even more preferably 140 minutes or less.

[0175] By sufficiently impregnating the raw material sheet with a catalyst, setting the temperature to a suitable heating temperature, and adjusting the heating treatment time, the degree of progress of pore formation can be controlled, and physical properties as a porous body, such as specific surface area, volume of various pores, and average pore diameter, can be controlled.

[0176] If the heat treatment time is less than the above lower limit, carbonization is likely to be insufficient.

[0177] In addition, as a heat treatment, after the heat treatment as described above (which may be referred to as the first heat treatment), an additional reheat treatment may be performed in a predetermined gas atmosphere. That is, the carbonization treatment may be performed by dividing the heat treatment into multiple stages with different conditions, such as temperature. By performing the first heat treatment and the reheat treatment under predetermined conditions, the physical properties can be adjusted, and the reactivation after carbonization can proceed more effectively, thereby obtaining an activated carbon fiber sheet with excellent adsorption and desorption properties.

[0178] 4-4. Resurrection Treatment

[0179] In the present invention, the reactivation treatment can be performed, for example, by supplying steam, carbon dioxide, or an alkaline agent continuously after the heat treatment and holding at an appropriate reactivation temperature for a predetermined time, thereby obtaining an activated carbon fiber sheet.

[0180] The lower limit of the revival temperature may preferably be 300°C or higher, more preferably 350°C or higher, and even more preferably 400, 500, 600, 700, or 750°C or higher.

[0181] On the other hand, the upper limit of the revival temperature may preferably be 1400°C or lower, more preferably 1300°C or lower, and even more preferably 1200°C or 1000°C or lower.

[0182] In addition, when performing a revitalization treatment continuously after a heat treatment, it is desirable to adjust the temperature to be equivalent to that of the heat treatment temperature.

[0183] The lower limit of the revival time may preferably be 1 minute or more, and more preferably 5 minutes or more.

[0184] The upper limit of the revival time may be arbitrary, but preferably 180 minutes or less, more preferably 160 minutes or less, even more preferably 140 minutes or less, 100 minutes or less, 50 minutes or less, or 30 minutes or less.

[0185] 4-5. Fabrication of Molded Bodies

[0186] The processing method for a molded body comprising an adsorbent containing activated carbon fibers and a binder is not particularly limited, but, for example, it can be obtained by preparing a mixture of both and molding it. In one embodiment, a molded body can be produced, for example, as follows.

[0187] <Preparation of a slurry containing activated carbon fibers and a binder>

[0188] A pre-prepared activated carbon fiber sheet and a binder can be mixed in water, and then defiberized and dispersed using a mixer to mix the two, thereby obtaining a slurry containing both. Depending on the size of the mixer, the activated carbon fiber sheet to be fed into the mixer may be cut into small pieces of an appropriate size before feeding.

[0189] <Formation of the molded body>

[0190] A slurry containing activated carbon fibers and a binder obtained as described above can be poured into a mold of a desired shape, dehydrated while applying pressure, and then dried to obtain a molded adsorbent.

[0191] Examples

[0192] The present invention will be explained more specifically below with reference to examples, but the technical scope of the present invention is not limited to the following examples.

[0193] Various items regarding the physical properties and performance of activated carbon fibers were measured and evaluated using the methods described below. In addition, various numerical values ​​defining the present invention can be obtained by the measurement and evaluation methods below.

[0194] <Fiber Diameter>

[0195] Fiber diameter was determined by using a scanning electron microscope JSM-IT300 InTouchScope (manufactured by Nippon Denshi Co., Ltd.), randomly sampling 10 fibers from 500x images, measuring them, and then calculating the average value.

[0196] Fiber Length · Average Value

[0197] Fiber length was measured using a DIGITAL MICROSCOPE KH-8700 (manufactured by Hyrox Co., Ltd.), 20 fibers were randomly selected from a 50x magnification image, and the average value was calculated.

[0198] Fiber Length · Standard Deviation

[0199] Fiber length was measured using a DIGITAL MICROSCOPE KH-8700 (manufactured by Hyrox Co., Ltd.), 20 fibers were randomly selected from a 50x magnification image, and the standard deviation was calculated.

[0200] <Fiber Length and Coefficient of Variation>

[0201] It was calculated from the standard deviation / mean value.

[0202] Specific surface area

[0203] Approximately 30 mg of a measurement sample (such as an activated carbon fiber sheet) was taken, vacuum dried at 200°C for 20 hours, weighed, and measured using a high-precision gas / vapor adsorption measuring device, BELSORP-max II (Microtrack Bell). The amount of nitrogen gas adsorbed at the boiling point of liquid nitrogen (77K) was... at a relative pressure of 10 -8 The adsorption isotherm of the sample was constructed by measuring in the range of 0.990. This adsorption isotherm was analyzed by the BET method, which automatically determines the analysis relative pressure range as the condition of the adsorption isotherm type I (ISO9277), and the BET specific surface area per weight (unit: m² / g) was calculated and set as the specific surface area (unit: m² / g).

[0204] <Total Crafting Volume>

[0205] The total pore volume (unit: cm³ / g) in the one-point method was calculated from the result of the isothermal adsorption line obtained from the above specific surface area term at a relative pressure of 0.960.

[0206] <Average pore diameter (Average pore diameter)>

[0207] It was calculated by the following Equation 3.

[0208] Average pore diameter (unit: nm) = 4 × total pore volume × 10 3 ÷ Specific Surface Area … Equation 3

[0209] Ultramicroscopic volume

[0210] The isothermal adsorption line obtained from the above specific surface area term was analyzed using the GCMC method with the analysis settings set to “smoothing (moving average processing using one point before and after the entire point of analysis of the pore distribution)”, “distribution function: No-assumption”, “definition of pore diameter: Solid and Fluid Def. Pore Size”, and “Kernel: Slit-C-Adsorption” using the analysis software BELMaster attached to the high-precision gas / vapor adsorption measuring device BELSORP-max II (Microtrack BEL). From the result of the pore distribution curve obtained during adsorption, the integrated pore volume of 0.7 nm was read and set as the ultramicro pore volume (unit: cm³ / g).

[0211] Microsphere Volume

[0212] The isothermal adsorption line obtained from the above specific surface area term was analyzed using the GCMC method with the analysis settings set to “smoothing (moving average processing using one point before and after the entire point of analysis of the pore distribution)”, “distribution function: No-assumption”, “definition of pore diameter: Solid and Fluid Def. Pore Size”, and “Kernel: Slit-C-Adsorption” using the analysis software BELMaster attached to the high-precision gas / vapor adsorption measuring device BELSORP-max II (Microtrack BEL). From the result of the pore distribution curve obtained during adsorption, the integrated pore volume of 2.0 nm was read and set as the micropore volume (unit: cm³ / g).

[0213] <Measuring the dimensions of the molded suction cup>

[0214] After leaving the molded adsorbent in an environment with a humidity of 23±2℃ and a relative humidity of 50±5% for more than 12 hours, the size of the molded adsorbent was measured by taking dimensions using a vernier caliper and a ruler. In addition, the weight of the molded adsorbent was measured using an electronic balance.

[0215] Density of molded adsorbents

[0216] It was calculated by the following Equation 4.

[0217] <Equation 4>

[0218] Density (Unit: g / cm³) = Weight of molded adsorbent ÷ Volume of molded adsorbent × 100

[0219] The volume of the molded adsorbent was calculated from the results of measuring the dimensions of the molded adsorbent or obtained from the size of the mold of the molded adsorbent.

[0220] Moisture content

[0221] After the measurement sample was left standing for more than 12 hours in an environment with a temperature of 23±2℃ and a relative humidity of 50±5%, 0.5~1.0g of the sample was collected and dried in a dryer at 115±5℃ for more than 3 hours, the moisture content (unit: %) was calculated from the weight change.

[0222] <n-부탄 흡탈착 성능>

[0223] Based on the American Society for Testing Materials Standard Test Method for Determination of Butane Working Capacity of Activated Carbon (ASTMD5228-16), the concentration of n-butane gas, the flow rate, and the flow rate of desorbing air were independently set and tested.

[0224] The molded adsorbent was dried in a dryer at 115±5℃ for at least 3 hours, and the dry weight was measured after cooling. After measuring the mass of an empty adsorption container (a stainless steel frame container with a cross-sectional shape identical to that of the molded adsorbent and capable of gas flow), the molded adsorbent was filled into the adsorption container.

[0225] Next, the test tube was placed in a flow device, and at a test temperature of 25°C, 1.0 L / min of n-butane gas diluted with air to a concentration of 0.2% was flowed into the test tube to adsorb n-butane. The test tube was removed from the flow device and its mass was measured. This flow of 0.2% concentration n-butane gas was repeated until a certain mass was achieved, that is, until the amount of adsorption was saturated.

[0226] The test tube was reinstalled in the flow device, and 20.0 L / min of air was flowed through the test tube for 12 minutes at a test temperature of 25°C to desorb n-butane. The test tube was removed from the flow device and its mass was measured.

[0227] Measurement of <0ppm retention time>

[0228] The changes in adsorption and desorption concentrations when this n-butane was distributed were measured every 6 seconds using a portable gas detector Cosmotector (model number: XP-3160, manufacturer: Shin-Cosmos Denki Kabushiki Kaisha).

[0229] After repeating the first adsorption and desorption, regarding the change in concentration of the second adsorption, if it is less than the lower limit of quantification (25 ppm), it is set to 0 ppm, and the time maintained at 0 ppm from the beginning is set to the 0 ppm maintenance time (min).

[0230] The adsorption and desorption operations were repeated a total of two times, and the first adsorption amount, effective adsorption / desorption amount, effective adsorption / desorption rate, and effective adsorption / desorption rate were calculated using the following equations 5, 6, and 7.

[0231] <Equation 5>

[0232] 1st adsorption amount = 1st n-butane adsorption amount

[0233] In addition, the units of each value are as follows.

[0234] 1st n-butane adsorption amount (Unit: g)

[0235] <Equation 6>

[0236] Effective adsorption / desorption amount = (2nd n-butane adsorption amount + 2nd n-butane desorption amount) ÷ 2

[0237] In addition, the units of each value are as follows.

[0238] Effective adsorption / desorption amount (unit: g)

[0239] 2nd n-butane adsorption amount (Unit: g)

[0240] 2nd n-butane desorption amount (Unit: g)

[0241] <Equation 7>

[0242] Effective adsorption / desorption rate = Effective adsorption / desorption amount ÷ Dry weight of molded adsorbent × 100

[0243] In addition, the units of each value are as follows.

[0244] Effective adsorption / desorption rate (Unit: wt%)

[0245] Effective adsorption / desorption amount (unit: g)

[0246] Dry weight of molded adsorbent (Unit: g)

[0247] <Equation 8>

[0248] Effective adsorption / desorption rate = Effective adsorption / desorption amount ÷ 1st adsorption amount × 100

[0249] In addition, the units of each value are as follows.

[0250] Effective adsorption / desorption rate (Unit: %)

[0251] Effective adsorption / desorption amount (unit: g)

[0252] 1st adsorption amount (unit: g)

[0253] <Example 1>

[0254] (1.1) Activated carbon fiber

[0255] Rayon fibers (56 dtex, fiber length 102 mm) on a web with a basis weight of 400 g / m² were impregnated with a 6-10% aqueous solution of disammonium hydrogen phosphate using a carding machine, and after mixing and drying, 8-10% by weight was attached. The obtained pre-treated fibers were heated to 900°C in 45 minutes under a nitrogen atmosphere and held at this temperature for 3 minutes. Subsequently, at that temperature, an activation treatment was performed for 17 minutes in a nitrogen stream containing water vapor with a dew point of 71°C to obtain activated carbon fibers.

[0256] (1.2) Molded adsorbent

[0257] As a binder, 5 parts by weight of 50 TWF acrylic fiber manufactured by Nihon Exlan Kogyo Co., Ltd. were placed in a mixer with 0.5 L of water and defiberized and dispersed for 30 seconds. Then, 100 parts by weight of the activated carbon fiber obtained in (1.1) and 0.5 L of water were added and defiberized and dispersed for an additional 10 seconds, thereby obtaining a slurry (first slurry) in which the defiberized activated carbon fiber is dispersed. A metal cylinder with an inner diameter of 63 mm and a height of 400 mm, which can be divided at a position 18 mm from the bottom, was placed on a funnel equipped with a perforated plate for suction dewatering, and the first slurry was injected into the metal cylinder, and then dewatered by suction from the bottom to form. From a metal cylinder, a bottom section of 18 mm containing a molded body in a wet state was divided, the upper and lower ends of the metal cylinder were placed between punching plates and a 1 kg weight was placed on top, and the molded body was compressed to a height of 18 mm. After drying at 120°C for 4 hours, the metal cylinder was removed to obtain a disc-shaped adsorbent with an outer diameter of 62 mm and a height of 18 mm. The obtained molded adsorbent was less prone to shape collapse than activated carbon fiber.

[0258] <Example 2>

[0259] (1.1) Activated carbon fiber

[0260] A needle-punched nonwoven fabric with a basis weight of 400 g / m² made of rayon fibers (17 dtex, fiber length 76 mm) was impregnated with a 6-10% aqueous solution of disammonium hydrogen phosphate, mixed, dried, and attached at a weight of 8-10%. The obtained pre-treated nonwoven fabric was heated to 900°C over 40 minutes in a nitrogen atmosphere and held at this temperature for 3 minutes. Subsequently, an activation treatment was performed for 17 minutes in a nitrogen stream containing water vapor with a dew point of 71°C at that temperature to obtain an activated carbon fiber sheet.

[0261] (1.2) Molded adsorbent

[0262] A molded adsorbent was obtained in the same manner as in Example 1, except that the activated carbon fiber obtained in (1.1) above was used.

[0263] <Example 3>

[0264] (1.1) Activated carbon fiber

[0265] A needle-punched nonwoven fabric with a basis weight of 400 g / m² made of rayon fibers (7.8 dtex, fiber length 76 mm) was impregnated with a 6-10% aqueous solution of disammonium hydrogen phosphate, mixed, dried, and attached at a weight of 8-10%. The obtained pre-treated nonwoven fabric was heated to 900°C over 45 minutes in a nitrogen atmosphere and held at this temperature for 3 minutes. Subsequently, an activation treatment was performed for 17 minutes in a nitrogen stream containing water vapor with a dew point of 71°C at that temperature to obtain an activated carbon fiber sheet.

[0266] (1.2) Molded adsorbent

[0267] A molded adsorbent was obtained in the same manner as in Example 1, except that the activated carbon fiber sheet obtained in (1.1) above was used.

[0268] <Example 4>

[0269] (1.1) Activated carbon fiber

[0270] An activated carbon fiber sheet was obtained in the same manner as in Example 3, except that a needle-punched nonwoven fabric with a basis weight of 400 g / m² made of rayon fibers (5.6 dtex, fiber length 76 mm) was used.

[0271] (1.2) Molded adsorbent

[0272] A molded adsorbent was obtained in the same manner as in Example 1, except that the activated carbon fiber sheet obtained in (1.1) above was used.

[0273] <Example 5>

[0274] (1.1) Activated carbon fiber

[0275] Activated carbon fibers were obtained in the same manner as in Example 1 above.

[0276] (1.2) Molded adsorbent

[0277] 5 parts by weight of the binder used in Example 1 were placed in a mixer with 0.5 L of water and defiberized and dispersed for 30 seconds, and 60 parts by weight of the activated carbon fiber of (1.1) and 0.5 L of water were added and defiberized and dispersed for an additional 10 seconds to obtain a first slurry.

[0278] Next, 40 parts by weight of granular activated carbon (specific surface area 1660 m² / g, average particle diameter 502 μm, standard deviation 89 μm) were added to the first slurry and stirred with a spatula to obtain a second slurry in which activated carbon fibers and granular activated carbon were dispersed. The second slurry was dehydrated by suction and dried in the same manner as in Example 1 to obtain a disc-shaped molded adsorbent with an outer diameter of 62 mm and a height of 18 mm. The obtained molded adsorbent was less prone to shape collapse than the activated carbon fibers.

[0279] <Example 6>

[0280] (1.1) Activated carbon fiber

[0281] Activated carbon fibers were obtained in the same manner as in Example 2 above.

[0282] (1.2) Molded adsorbent

[0283] A molded adsorbent was obtained in the same manner as in Example 5, except that the activated carbon fiber obtained in (1.1) above was used.

[0284] <Example 7>

[0285] (1.1) Activated carbon fiber

[0286] An activated carbon fiber sheet was obtained in the same manner as in Example 3 above.

[0287] (1.2) Molded adsorbent

[0288] A molded adsorbent was obtained in the same manner as in Example 5, except that the activated carbon fiber sheet obtained in (1.1) above was used.

[0289] <Example 8>

[0290] (1.1) Activated carbon fiber

[0291] An activated carbon fiber sheet was obtained in the same manner as in Example 4 above.

[0292] (1.2) Molded adsorbent

[0293] A molded adsorbent was obtained in the same manner as in Example 5, except that the activated carbon fiber sheet obtained in (1.1) above was used.

[0294] <Comparative Example 1>

[0295] (1.1) Activated carbon fiber

[0296] A needle-punched nonwoven fabric with a basis weight of 300 g / m² made of rayon fibers (3.3 dtex, fiber length 76 mm) was impregnated with a 6-10% aqueous solution of disammonium hydrogen phosphate, mixed, dried, and attached at a weight of 8-10%. The obtained pre-treated nonwoven fabric was heated to 900°C over 50 minutes in a nitrogen atmosphere, and then reactivated for 13 minutes in a nitrogen stream containing water vapor with a dew point of 60°C at that temperature to obtain an activated carbon fiber sheet.

[0297] (1.2) Molded adsorbent

[0298] A molded adsorbent was obtained in the same manner as in Example 1, except that the activated carbon fiber sheet obtained in (1.1) of Comparative Example 1 above was used.

[0299] <Comparative Example 2>

[0300] 5 parts by weight of the binder used in Example 1 were placed in a mixer with 0.5 L of water and defiberized and dispersed for 30 seconds. Then, 100 parts by weight of the granular activated carbon used in Example 5 and 0.5 L of water were added and stirred with a spatula to obtain a granular activated carbon adsorption slurry. This adsorption slurry was dehydrated by suction and dried in the same manner as in Example 1 to obtain a disc-shaped molded adsorbent with an outer diameter of 62 mm and a height of 18 mm.

[0301] Measurement of Pressure Loss

[0302] Molded adsorbents of Examples 1 to 8 and Comparative Examples 1 and 2 were prepared.

[0303] As a container for housing a molded adsorbent, a cylindrical frame body (frame container) was prepared, in which one side and the opposite side are open for ventilation. A frame container with a diameter of one side of 6.2 cm was prepared.

[0304] The prepared molded adsorbent was filled into the inside of a frame container without any gaps and used as a test sample to measure pressure loss.

[0305] Pressure loss was measured as follows. Air at a rate of 60 L / min was passed through the test sample prepared as above, and the result of measuring the differential pressure at the inlet and outlet of the test sample using a testo 510 differential pressure gauge (Test Co., Ltd.) was recorded as the pressure loss (kPa).

[0306] Various measurement results for molded adsorbents are shown in Tables 1-1 to 1-7.

[0307] [Table 1-1]

[0308]

[0309] [Table 1-2]

[0310]

[0311] [Table 1-3]

[0312]

[0313] [Table 1-4]

[0314]

[0315] [Table 1-5]

[0316]

[0317] [Table 1-6]

[0318]

[0319] [Table 1-7]

[0320] Explanation of the symbols

[0321] 1 Laminated adsorbent, 10 Sheet-shaped molded adsorbent, 10a Main surface of the sheet-shaped molded adsorbent, 10b Side cross-section of the sheet-shaped molded adsorbent, 10c Side cross-section of the sheet-shaped molded adsorbent, F Direction of gas flow, 2 Disc-shaped molded adsorbent, 3 Circular molded adsorbent

Claims

Claim 1 A molded adsorbent for a canister, wherein the molded adsorbent comprises an adsorbent containing activated carbon fibers and a fibrous binder, wherein the defibrillated activated carbon fibers and the fibrous binder are intertwined to form the adsorbent containing activated carbon fibers and the fibrous binder, wherein the content ratio of the adsorbent containing activated carbon fibers and the fibrous binder is 0.3 to 20 parts by weight of the fibrous binder per 100 parts by weight of the adsorbent containing activated carbon fibers, wherein the fiber diameter of the activated carbon fibers is 13.0 μm or more, and the effective adsorption / desorption rate of n-butane of the molded adsorbent is 50% or more. Claim 2 A molded adsorbent according to claim 1, wherein the fiber material serving as a precursor to the activated carbon fiber has a fineness of 4.0 to 60.0 dtex. Claim 3 A molded adsorbent according to claim 1, wherein the specific surface area of ​​the activated carbon fiber is 1110 to 2300 m² / g. Claim 4 A molded adsorbent according to claim 1, wherein the total pore volume of the activated carbon fiber is 0.50 to 1.20 cm³ / g. Claim 5 A molded adsorbent according to claim 1, wherein the pore volume of the pores of the activated carbon fiber, having a pore diameter greater than 0.7 nm and less than or equal to 2.0 nm, is 0.20 to 1.20 cm³ / g. Claim 6 In claim 1, the ratio of the pore volume R of the activated carbon fiber 0.7 / 2.0 This is 15% or more and less than 50%, and the above R 0.7 / 2.0 A molded adsorbent, which is a ratio expressed as the pore volume of pores with a pore diameter of 0.7 nm or less, which occupies the pore volume of pores with a pore diameter of 2.0 nm or less. Claim 7 A canister having a molded adsorbent as described in any one of paragraphs 1 to 6. Claim 8 In paragraph 7, the above canister is a canister for automobiles.

Citation Information

Patent Citations

  • Molded adsorbent and its production

    JP1993103979A

  • Active carbon fiber non-woven fabric, and element using said non-woven fabric

    KR1020140098122A

  • Activated carbon fiber sheets for automotive canisters

    KR1020210020138A